Pemikiran Tentang Hakikat Tujuan Pendidikan Islam di Era 5.0 - Hamdiani (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The Society 5.0 era, which integrates smart technology into human life, brings new challenges and opportunities for education, including Islamic education. The essence of the goal of Islamic education in this era is to shape a generation that is balanced in spiritual, intellectual, and moral aspects, possessing the ability to utilize technology wisely. Islamic education plays a crucial role in preserving religious and cultural values ​​while simultaneously fostering innovation and adaptation to the changing times. This study aims to analyze the essence of the goals of Islamic education in the Society 5.0 era and the role of Islamic education in social transformation within this context. The research employs a literature review method, utilizing data obtained from various books, literature, documents, journals, articles, and information from print and electronic media relevant to the issues under examination. The findings indicate that, firstly, the essence of the goal of Islamic education in the Society 5.0 era is to cultivate a generation that is knowledgeable, possesses good character, and is capable of utilizing technology for the benefit of the community (ummah) while remaining steadfast in Islamic values. Secondly, Islamic education in the Society 5.0 era must meet several key requirements, including the optimal use of technology and modernization in transforming the Islamic education system.